2002
DOI: 10.1002/car.725
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting children's disclosure of secrets in an investigatory interview

Abstract: The present study aimed to identify how children's understanding of the investigatory interview process influenced their disclosure of secrets. Forty-four 6-year-and 7-year-old children participated in the study. Four short stories were read to each child. The stories were about young children who witnessed an event (e.g. witnessing a person stealing a pizza) and were asked to keep the witnessed event secret, then they were interviewed by an authority figure (e.g. security guard) and asked repeatedly about wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
2
10
1
Order By: Relevance
“…Although answerable questions resulted in lower levels of change, children still altered their responses to approximately one-tenth of such questions. This reinforces the assumption that if children are asked questions more than once, they feel pressured to alter their answers (Hartwig & Wilson, 2002;Home OYce, 2001).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Although answerable questions resulted in lower levels of change, children still altered their responses to approximately one-tenth of such questions. This reinforces the assumption that if children are asked questions more than once, they feel pressured to alter their answers (Hartwig & Wilson, 2002;Home OYce, 2001).…”
Section: Discussionsupporting
confidence: 66%
“…The opinion-seeking questions did not have speciWc answers; therefore, if children were to answer an opinion-seeking question consistently, they needed to remember and maintain the response they gave the Wrst time the question was asked. Children's failure to maintain original opinions might reXect their compliance; Hartwig and Wilson (2002) found that children assume that if an interviewer repeats a question, the interviewer is implying that the Wrst answer was wrong or needs to be changed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unlike Quas and colleagues’ participants, children in our study watched a video of their first interview before being questioned a second time. As a result, it is possible that children were confused as to why the interviewer was asking the same questions again, and therefore interpreted the repeated questions as a signal to change their previous responses (Donaldson, 1982; Hartwig & Wilson, 2002; Lyons, 2002; Rose & Blank, 1974; Siegal et al ., 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research has explored the conditions under which repeated questions could influence memory performance of children in recalling an event (Memon & Vartoukian 1996; Hartwig & Wilson 2002; Krähenbühl & Blades 2006). Hartwig and Wilson examined factors that may affect children's disclosure of secrets in an investigatory interview.…”
Section: Repetition and Interviewsmentioning
confidence: 99%